FEES‐based assessment of pharyngeal hypesthesia—Proposal and validation of a new test procedure. Issue 11 (5th August 2019) - Labeit, Bendix; Muhle, Paul; Ogawa, Mao; Claus, Inga; Marian, Thomas; Suntrup‐Krueger, Sonja; Warnecke, Tobias; Schroeder, Jens Burchard; Dziewas, Rainer
Abstract: Background: Intact pharyngeal sensation is essential for a physiological swallowing process, and conversely, pharyngeal hypesthesia can cause dysphagia. This study introduces and validates a diagnostic test to quantify pharyngeal hypesthesia. Methods: A total of 20 healthy volunteers were included in a prospective study. Flexible endoscopic evaluation of swallowing (FEES) and a sensory test were performed both before and after pharyngeal local anesthesia. To test pharyngeal sensation, a small tube was positioned transnasally in the upper third of the oropharynx with contact to the lateral pharyngeal wall. Increasing volumes of blue‐dyed water were injected through the tube, and the latency of swallowing response (LSR) was determined by two independent raters from the endoscopic video recording. Three trials were performed for each administered volume starting with 0.1 mL and increased by 0.1 mL up to 0.5 mL. Key Results: The average LSR without anesthesia was 2.24 ± 0.80 s at 0.1 mL, 1.79 ± 0.84 s at 0.2 mL, 1.29 ± 0.62 s at 0.3 mL, 1.17 ± 0.41 s at 0.4 mL, and 1.19 ± 0.52 s at 0.5 mL. With anesthesia applied, the average LSR was 2.65 ± 0.62 s at 0.1 mL, 2.64 ± 0.49 s at 0.2 mL, 2.44 ± 0.65 s at 0.3 mL, 2.10 ± 0.80 s at 0.4 mL, and 2.18 ± 0.85 s at 0.5 mL. LSR was significantly longer following anesthesia at 0.2 mL (t = −3.82; P = .001), 0.3 mL (t = −4.65; P < .000), 0.4 mL (t = −5.77; P < .000), and 0.5 mL (t = −3.49; P = .005). Conclusion and Inferences: Pharyngeal hypesthesia can be quantified with sensory testing using LSR. Suitable volumes to distinguish between normal and impaired pharyngeal sensation are 0.2 mL, 0.3 mL, 0.4 mL and 0.5 mL. Experimentally induced pharyngeal anesthesia represents a valid model of sensory dysphagia. Abstract : Schematic view of the transnasal tube in the upper third of the oropharynx with contact of the tip to the lateral pharynx wall during the sensory test. Reprinted with permission from the authors, copyright Heike Blum, Department of Neurology, University Hospital Münster)